Keefektifan Kelompok Psikoedukasi dengan Teknik Modeling untuk Meningkatkan Keterampilan Sosial Siswa - Yuwinda Ardila; Anwar Sutoyo; Mulawarman Mulawarman (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
This study aims to test and analyze the effectiveness of psychoeducation group services with modeling techniques to improve students' social skills. This study uses a non-equivalent group pre-test post-test control group design. The random assignment sampling technique was used to select 10 experimental subjects placed into two groups so that each group consisted of five students. Data collection using the goal attainment scale (GAS), the results of the coefficient regression test of the ANOVA test showed that the psychoeducation group services of modeling techniques were effective in improving the social skills of students who obtained F tables = 4.46; with p <0.05 so that the experimental group proved to have a significant effect with a value of F = 73,164; p = 0.00 while the control group F = 4.151; p = 0.76. The findings of this study confirm that psychoeducation group services with effective modeling techniques to improve students' social skills.